The Tradition of Eating bajamba in Stimulating Early Childhood Social Emotional Development - Nusir, Lidia; Misbah Laila; Tria Marini (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Children's social emotional development that needs to be stimulated by emphasizing aspects of 3 things, namely self-awareness, responsibility and prosocial behavior. This can be stimulated through the traditional activities of eating bajamba which is a tradition of the Minangkabau people through eating together around the talam (dulang) by sitting cross-legged for men and kneeling for women. The purpose of this study is to analyze how the traditional activities of eating bajamba in stimulating aspects of early childhood social emotional development. This research uses a qualitative method with a phenomenological approach. Data collection techniques use interviews, observation and documentation, while data analysis techniques go through a process of data reduction, data presentation and drawing conclusions. This study found that through the tradition of eating bajamba, children's social emotional development in terms of self-awareness, responsibility and prosocial behavior can be stimulated properly. Seen in the observation results, the majority of children in the aspect of self-awareness achieved 80% stimulation, 70% in the aspect of responsibility, and 75% in the aspect of prosocial behavior. Each of these indicator achievements is obtained through bajamba eating activities from the beginning to the end of the activity. In addition, this program helps children appreciate culture more, and build more harmonious relationships with friends and family.